Comparison of unique effects of two contrasting types of cellulose nanomaterials on setting time, rheology, and compressive strength of cement paste. (October 2021) - Nassiri, Somayeh; Chen, Zhen; Jian, Guoqing; Zhong, Tuhua; Haider, Md Mostofa; Li, Hui; Fernandez, Carlos; Sinclair, Michael; Varga, Tamas; Fifield, Leonard S.; Wolcott, Michael
Abstract: Cellulose nanomaterials (CNMs) by different production methods have been studied in cementitious systems, but the effects of contrasting types of CNMs on cement properties have not been delineated. This study is a side-by-side comparison of rheology, setting times, and compressive strength of cement paste incorporated with cellulose nanocrystals (CNCs) from acid hydrolysis vs. mechanically fibrillated cellulose nanofibers (CNFs). This study demonstrates that CNF gels increase the viscosity of cement paste (control) due to the entangled nanofiber network. In contrast, the shorter and more mobile CNCs reduce the viscosity and provide longer slump retention than a polycarboxylate superplasticizer. CNCs work as a set retarder, but CNFs show about half the deferring effect on setting times. Both CNMs delivered a similar increase in compressive strength (17–18%), but their optimum amount differed in conjunction with their respective morphology and percolation limits. This study underscores the distinct effects of CNCs vs. CNFs and shows, indeed, these different nanomaterials have contrasting effects on various properties of the cement paste and should be appropriately specified for concrete applications.